Pendampingan Industri Perumahan Lumpia Sebagai Oleh-Oleh Khas Semarang - Imron Widjaja; Tan Winda; Iswahyudi Iswahyudi (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2023)
The food souvenir industry in Semarang is currently dominated by several well-known celebrity brands. This large capital business hampers the competitiveness of the local souvenir home food industry. This community partnership program works with home industry partners